1986
DOI: 10.1002/1097-4679(198609)42:5<699::aid-jclp2270420503>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and intellectual correlates of unsuccessful suicide attempts in people with epilepsy

Abstract: This study evaluated the emotional and intellectual correlates of unsuccessful suicide attempts in persons with seizure disorders. Psychosocial evaluations were completed on 198 adults with epilepsy, of whom 32 had made one or more suicide attempts. The MMPI demonstrated increased anxiety and decreased ego strength among those with histories of suicide attempts in comparison to those without such a history. Intellectual abilities as evaluated by the WAIS were slightly lower among the suicide attempters, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
3

Year Published

1989
1989
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 10 publications
1
9
0
3
Order By: Relevance
“…Early onset of epilepsy also has been associated with depression, marital status, and perceived stigma (18). No association between duration of epilepsy and relative risk of suicide was found in the present study, in keeping with a study by Batzel and Dodrill (38). Mendez et al (16) compared 62 patients with epilepsy and psychosis with 62 mentally well patients with epilepsy and found the mean age at epilepsy onset among psychotic patients to be 13 years, compared with 9 years in the control group.…”
Section: Discussionsupporting
confidence: 89%
“…Early onset of epilepsy also has been associated with depression, marital status, and perceived stigma (18). No association between duration of epilepsy and relative risk of suicide was found in the present study, in keeping with a study by Batzel and Dodrill (38). Mendez et al (16) compared 62 patients with epilepsy and psychosis with 62 mentally well patients with epilepsy and found the mean age at epilepsy onset among psychotic patients to be 13 years, compared with 9 years in the control group.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, neuroticism at age 14, was shown to be a useful marker of the risk of attempts at age 21 (48). Related constructs, positive and negative emotionality (96, 162, 168), emotional instability (166), and anxiety measures (130, 173, 174) were also associated with the risk of attempts. Nevertheless, in a large‐community study ( N = 5877), encompassing diverse age groups and controlling for a number of psychiatric and sociodemographic factors, neuroticism was not related to attempts (152), nor was it related to future suicide risk in depressed patients in an 18‐year‐long prospective study (175).…”
Section: Resultsmentioning
confidence: 99%
“…Batzel and Dodrill [37] observed increased rates of suicide attempts among patients with anxiety, other emotional problems, and lower intelligence. The authors of this study suggested that availability of substantial quantities of antiepileptic medications with which a suicide attempt may be undertaken increased risk for suicide among these patients.…”
Section: Multiple Sclerosismentioning
confidence: 99%